Bibliometric analysis of research trends on disability in Indonesia - Hafiar, Hanny; Aulianto, Dwi Ridho; Lukman, Syauqy; Amin, Kholidil (Jurnal Kajian Informasi dan Perpustakaan, 2023)
Indonesian people have a unique perception of understanding the concept of disability. Researchers use various terminologies to address topics of disabilities in their published studies. There is no national roadmap for disability research that may integrate and guide studies on the subject. This study investigated scientific outputs made by academics researching disabilities topics in Indonesia. Publications on topics of disabilities it found 3,220 publications, indexed in the national indexing service “Garuda” (abbreviation for Garba Rujukan Digital, meaning: Digital Reference Portal), published from 2010 to 2019. This study employed a bibliometric approach, browsing and analyzing numerical trends of several publications, quantitative distribution of publication years, authors’ characteristics, publishers, subject names, and keywords used. Findings research were compared with relevant references to provide a holistic picture of trends in disability studies over the last decade. Research result showed that the number of publications increased significantly from 2010 to 2019, and discussions on relevant and current disabilities conditions progressed according to the development of national and global works on the subject. Most studies focus on educational topics, dictating publication trends, with some published works, authors, subjects, and keywords being dominated by disability papers on education, with authors and publishers from western Indonesia dominantly publishing a significantly higher number of publications than their counterparts in the central and eastern parts. This study concludes that research trends on disability in Indonesia show significant development from year to year regarding the number of publications, the distribution of authors, and subject specifics.